PS02.082: OPTIMAL TIMING FOR ASSESSMENT OF TUMOR RESPONSE TO NCRT WITH MRI IN PATIENTS WITH ESOPHAGEAL CANCER. (14th September 2018) - Borggreve, Alicia; Heethuis, S; Goense, L; Van Rossum, P; Van Lier, A L H M W; Hillegersberg, Richard; Ruurda, Jelle; Lagendijk, J; Mook, Stella; Meijer, G J
Abstract: Background: Accurate identification of esophageal cancer patients with a pathologic complete response (pCR) following neoadjuvant chemoradiotherapy (nCRT) could enable safe omission of surgery in these patients. Diffusion-weighted (DW-)MRI imaging during the first 2–3 weeks of nCRT has shown promising results in the prediction of pCR to nCRT in esophageal cancer. However, the optimal timing of scanning for pathologic response prediction is unclear. The purpose of this study was to assess the optimal timing of DW-MRI scanning during nCRT to predict pCR. Methods: Consecutive patients with esophageal cancer undergoing nCRT (carboplatin/paclitaxel combined with 41.4Gy), followed by esophagectomy were eligible for inclusion in this prospective study. Patients underwent 6 sequential MRI scans of which one was performed prior to nCRT, and 5 were performed weekly during nCRT. The relative change in median tumor apparent diffusion coefficient (ADC) of the tumor on DW-MRI was determined at these six time points: ΔADC week(n) (%) = (ADCweek(n) -ADCbaseline )/ADCbaseline *100%. Response to nCRT was determined based on histopathologic evaluation of the resection specimen. Results: A total of 123 MRI scans of 21 patients with locally advanced esophageal cancer were analyzed. A pCR was found in 23.8% (5/21). Results of the linear mixed model analysis and logistic regression analysis (per week) are depicted in Table 1. The difference in tumor ADC values between pCR and non-pCR patients was most prominent in week 3 of nCRT (after 12–14 fractions, P = 0.04). Conclusion: The treatment-induced changes on DW-MRI during the first 3 weeks of nCRT appear to be the most promising for prediction of pCR in esophageal cancer patients. This information can be used in future DW-MRI validation studies, and eventually lead to accurate preoperative identification of pCR. Disclosure: All authors have declared no conflicts of interest.